THE PORTION OF AUTOLOGOUS BLOOD IN ORTHOPEDIC DEPARTMENT OF GENERAL HOSPITAL NOVA GORICA IN FIVE YEARS PERIOD (1996–2000) - Janka Černe-Zavadlav; Željko Mihelič; Albin Plahuta (Zdravniški Vestnik, 2002)
Background. The presentation of autologous blood donation with analysis of used blood and the percentage of autologous blood on Orthopedic Department in the years 1996–2000. Methods. From card-index of autologous blood donors we analysed 363 preoperative autologous blood donations.We followed the number of doses in one patient and type of operating procedure.We analysed the usage of blood from transfusion issue protocols and the usage of postoperative autotransfusion from patient protocols. Results. 91% of all preoperative blood donations in our hospital in five years period were from Orthopedic Department. There were 280 operating procedures (hip and knee arthroplasty) that needed blood transfusion. 196 of these (70%) were included in preoperative blood donation programme. We collected 330 doses: 1 dose in 61 cases, 2 doses in 100, 3 doses in 34 and 4 doses in 1 case or 1.68 doses per patient. The relationship between used autologous and allogenic blood were 46 : 54 (doses) or 38 : 62 (mL). Autologous blood represented 38% of all used blood on Orthopedic Department, only 11% of autologous blood were discarded. Conclusions. The program of preoperative blood donation is well organized on The Orthopedic Department of our Hospital. To our experience we make the most of profit of autotransfusion (to avoid risks of allogenic blood, optimal patient colaboration, low percentage of discarded blood) with two predonated doses in combination with postoperative autotransfusion. Regard to The Law of Blood supply (may 2000) we are going to introduce this protocol of preoperative blood donation for all programed operating procedures in our Hospital, which need blood transfusion.